Answer:
a) Sin (α + β) = [123/(17√61)] = 123 ÷ (17√61)
b) Cos (α + β) = [50/(17√61)] = 50 ÷ (17√61)
c) Sin (α - β) = [-27/(17√61)] = -27 ÷ (17√61)
d) Tan (α - β) = (-27/130)
Step-by-step explanation:
Sin α = (8/17) for (0 < α < π/2)
Cos β = [(6√61)/61] = (6/√61) for (0 < β < π/2)
Note that
Sin²x + Cos²x = 1
Sin²α + Cos²α = 1
(8/17)² + Cos²α = 1
Cos²α = 1 - (64/289) = (225/289)
Cos α = (15/17)
Sin²β + Cos²β = 1
Sin²β + (6/√61)² = 1
Sin²β = 1 - (36/61) = (25/61)
Sin β = (5/√61)
Sin α = (8/17)
Cos α = (15/17)
Sin β = (5/√61)
Cos β = (6/√61)
a) Sin (α + β) = Sin α Cos β + Sin β Cos α
= (8/17) × (6/√61) + (5/√61) × (15/17)
= [48/(17√61)] + [(75/(17√61)]
= [123/(17√61)]
= 123 ÷ (17√61)
b) Cos (α + β) = Cos α Cos β - Sin α Sin β
= (15/17) × (6/√61) - (8/17) × (5/√61)
= [90/(17√61)] - [40/(17√61)]
= [50/(17√61)]
= 50 ÷ (17√61)
c) Sin (α - β) = Sin α Cos β - Sin β Cos α
= (8/17) × (6/√61) - (5/√61) × (15/17)
= [48/(17√61)] - [(75/(17√61)]
= [-27/(17√61)]
= -27 ÷ (17√61)
d) Tan (α - β) = [Sin (α - β)] ÷ [Cos (α - β)]
Sin (α - β) = [-27/(17√61)] = -27 ÷ (17√61)
Cos (α - β) = Cos α Cos β + Sin α Sin β
= (15/17) × (6/√61) + (8/17) × (5/√61)
= [90/(17√61)] + [40/(17√61)]
= [130/(17√61)]
= 130 ÷ (17√61)
Tan (α - β) = [Sin (α - β)] ÷ [Cos (α - β)]
= [-27/(17√61)] ÷ [130/(17√61)]
= (-27/130)
Hope this Helps!!!